STRUCTURAL PARAMETER OPTIMIZATION OF LINE CONTACT STEEL STRAND INDUCTION HEATING COIL - CHENG YaPing; LI ZhiGang; ZHANG Qiang (Jixie qiangdu)
The relationship between the size of inner diameter of induction heating coil and induction heating result was analyzed based on the transformer series equivalent circuit model of induction heating coil,the data of induction heating result under different inner diameters were calculated by using finite element model,they were processed by using polynomial fitting method to get the best fit polynomial,the change law of the data was reflected. The result shows that the relationships between the temperature difference between center and surface,power and the size of inner diameter present a decreasing trend,the relationship between the heating time and the size of inner diameter presents a increasing trend. The inner diameter optimization model was established based on the best fit polynomial,the optimization model was solved by using genetic algorithms,the optimal solution of inner diameter is 49. 15 mm,it provides a theoretical basis for induction heating coil optimized design.